PENGARUH PAJAK KENDARAAN BERMOTOR TARIF PROGRESIF DAN PENDAPATAN WAJIB PAJAK TERHADAP DAYA BELI KONSUMEN KENDARAAN BERMOTOR RODA EMPAT (Studi Empiris Di Kantor SAMSAT Kota Jayapura) - Marice Waroi; Aaron M. A. Simanjuntak; Hastutie Noor Andrianti (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
This study aims to determine the Effect of Progressive Vehicle Taxes and Taxpayer Income on Consumer Purchasing Power. The research population is taxpayers who make motor vehicle tax payments in the Jayapura City Samsat Office. The number of samples is 70 people. Determination of the study sample using the nonprobability sampling method, data was collected by distributing questionnaires. The data analysis technique is multiple linear analysis. The results of the research conducted show that Progressive Vehicle Taxes have no significant positive effect on Consumer Purchasing Power, Taxpayer Income does not have a significant negative effect on Consumer Purchasing Power. The most dominant variable affects taxpayers regarding the tax on progressive tariff motor vehicles because they have a standard coefficient of beta 0 235.